2016
DOI: 10.1177/1049732315614294
|View full text |Cite
|
Sign up to set email alerts
|

Establishment, Implementation, and Consolidation of Clinical Pharmacy Services in Community Pharmacies

Abstract: When pharmacists incorporate clinical practice into their routine, barriers and facilitators influence the implementation of patient care services. Three focus groups were conducted with 11 pharmacists who were working for the Farmácia Popular do Brasil program on the establishment, implementation, and consolidation of clinical pharmacy services. The perception of the pharmacists in Brazil about the program was that it facilitated access to health care and medication. The distance between neighboring cities ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
54
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 53 publications
2
54
0
6
Order By: Relevance
“…The findings of this study, on the one hand, have confirmed the importance of pharmacists becoming members of the primary care team which is consistent with many international studies (Bradley et al., ; Dosea et al., ; Jorgenson, Laubscher, Lyons, & Palmer, ; Silcock, Raynor, & Petty, ). With a health system moving towards an interprofessional approach to primary care, pharmacists may contribute value to the team by delivering comprehensive medication management, providing health education and drug information for team members, patients and populations, and enhancing system efficiencies through cost‐effective and quality use of medicines (Dolovich et al., ).…”
Section: Discussionsupporting
confidence: 91%
“…The findings of this study, on the one hand, have confirmed the importance of pharmacists becoming members of the primary care team which is consistent with many international studies (Bradley et al., ; Dosea et al., ; Jorgenson, Laubscher, Lyons, & Palmer, ; Silcock, Raynor, & Petty, ). With a health system moving towards an interprofessional approach to primary care, pharmacists may contribute value to the team by delivering comprehensive medication management, providing health education and drug information for team members, patients and populations, and enhancing system efficiencies through cost‐effective and quality use of medicines (Dolovich et al., ).…”
Section: Discussionsupporting
confidence: 91%
“…and GPs' attitudes towards extended services in this review reflected international findings, where pharmacists in North America, Asia, Australasia, South America and Europe were also enthusiastic towards the concept of providing extended services (Dosea et al, 2017;Fang, Yang, Feng, Ni, & Zhang, 2011;Kinsey, Scahill, Bye, & Harrison, 2016;Kjome, Sandberg, & Granas, 2008;Schindel et al, 2017). Moreover, lack of awareness (Bjorkman, Viberg, Rydberg, & Stalsby Lundborg, 2008;Fakih, Marriott, & Hussainy, 2016;Freeman, Cottrell, Kyle, Williams, & Nissen, 2012;Wibowo, Sunderland, & Hughes, 2016), issues with community pharmacy premises (Babiker, Carson, & Awaisu, 2014;Bjorkman et al, 2008;Donald et al, 2017;Gray, Chamberlain, & Morris, 2016;Hattingh, Emmerton, Ng Cheong Tin, & Green, 2016;Murphy et al, 2016), lack of management support (Casserlie & Mager, 2016;Donald et al, 2017;Kinsey et al, 2016;Tsao et al, 2016;Watkins, McKee, Hughes, & Pfeiffenberger, 2017) and remuneration (Donald et al, 2017;Gray et al, 2016;Kinsey et al, 2016;Watkins et al, 2017) have also been found in other countries.…”
Section: Discussionsupporting
confidence: 61%
“…For instance, it is apparent that pharmacists are eager to expand their roles but lack the confidence to do so. Implementing regular training and increasing opportunities to apply training could enhance their confidence and reassure them of their competence (Donald et al, 2017;Dosea et al, 2017;Sim, Hattingh, Sherriff, & Tee, 2017;Watkins et al, 2017). Pharmacists' confidence could also be enhanced by having the ability to witness improved outcomes for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted nationally and internationally highlight the lack of confidence of pharmacists in delivering services directly to patients and the need for them to develop specific skills for the clinical practice [33][34][35][36]. Besides understanding the theoretical and philosophical foundation of the professional practice, these skills include knowledge about the pharmacotherapy for a number of different medical conditions [30].…”
Section: Discussionmentioning
confidence: 99%